Konflik Sosial Dalam Novel Samaran Karya Dadang Ari Murtono - Defri Yanus Waruwu; Nurizzati (Departemen Bahasa dan Sastra Indonesia dan Daerah, 2023)
The purpose of this study is to describe: (1) the forms of social conflict contained in Dadang Ari Murtono’s Samaran novel, (2) the causes of social conflict in Dadang Ari Murtono’s Samaran novel, (3) the impact of social conflict in Dadang Ari’s Samaran novel Murtono. This research is literary research and the method used in this research is descriptive method. The data in this study consist of words, phrases, clauses and sentences that describe the forms, causes and impacts of social conflict. Novel Samaran by Dadang Ari Murtono is the source of data in this study. The data collection stage in research begins with reading and understanding the novel, marking every utterance or words of each character and narrator or writer in the novel relating to the data being studied, to inventorying data related to the research problem. The triangulation technique is the technique used in this study. Data analysis was carried out in stages starting from classifying the data, then analyzing the data and interpreting the data, up to the stage of concluding the results of the research and writing a report on the results of the analysis. Based on the research that has been done, the research results obtained are: (1) the form of social conflict in the novel Samaran by Dadang Ari Murtono is in the form of conflict between religious believers, conflict between groups, and conflict between individuals. (2) The causes of social conflict in the novel Samaran Karya Dadang Ari Murtono are caused by differences between individuals, differences in social class, differences in interests, and social change. (3) The impact of social conflict in the novel Samaran by Dadang Ari Murtono includes the destruction of group unity, personality changes, and the destruction of social values ​​and norms.